Eating disorders as a public health issue: Prevalence and attributable impairment of quality of life in an Italian community sample. (August 2014) - Carta, Mauro Giovanni; Preti, Antonio; Moro, Maria Francesca; Aguglia, Eugenio; Balestrieri, Matteo; Caraci, Filippo; Dell'Osso, Liliana; Di Sciascio, Guido; Drago, Filippo; Faravelli, Carlo; Hardoy, Maria Carolina; D'Aloja, Ernesto; et al.
Abstract The prevalence of eating disorders (ED) in the community is still under debate, as well as the measure of their impact on the well-being of individuals. It was decided to evaluate the prevalence of eating disorders in an Italian community sample as well as to measure the burden of the quality of life of people and to compare it to those attributable to other chronic illnesses. A community survey of 4, 999 people using a questionnaire on health services utilization, the Advanced Neuropsychiatric Tools and Assessment Schedule (ANTAS), a semi-structured clinical interview derived from the non-patient version of the DSM-IV (SCID/NP) and Short Form Health Survey (SF-12) was conducted. A total of 3, 398 individuals were interviewed (68% of those recruited). Lifetime prevalence for overall ED was 1.7%; for anorexia 0.7%; for bulimia 0.6% and for binge eating disorder 0.5%. ED was more frequent in women than in men. No cases of anorexia in men were identified. ED showed an attributable burden in impairing quality of life with no statistically significant differences with those due to major depressive disorder, bipolar spectrum disorders and Wilson's disease. Of the pathological conditions considered, only multiple sclerosis showed a worsening attributable burden. ED thus has a non-negligible frequency in Italy, with severe impact on quality of life comparable to that produced by severe chronic psychiatric and general medical conditions. These elements emphasize that ED is a serious public health issue.